Phân tích văn bản viết của sinh viên Việt Nam trong nguồn ngữ liệu Valico phục vụ cho giảng viên dạy tiếng Italia ở môi trường nước ngoài = Scritti di Vietnamiti nel corpus di apprendenti valico un'analisi per il docente di italiano lingua straniera /Carla Marello,Trần Thu Trang. - Marello, Carla.
VALICO - Varietà di Apprendimento della Lingua Italiana Corpus Online – is the first database collecting Italian writings by foreign students with free access on the Internet since 2004. This database currently includes 382.098 words of 6.935 categories in 2502 texts. One fifth of the documents were written by Southeast Asian students, of which 145 texts were collected in Vietnam, 231 in Japan, 24 in Thailand. Besides, there are 106 texts written by Chinese students (collected in China and Italy). Typical features of this corpus include: Data are collected from images (stories told through 4-6 unscripted pictures and a drawing of a train station depicting various actions at different levels); The authors’ database of social linguistics can be searched simultaneously (for example, texts with verbs in subjunctive mood written by Spanish authors having learnt Italian for at least two years); Searching can be performed using geographical coordinates; The corpus of speakers of Italian VINCA (Varietà di Italiano di Nativi Corpus Appaiato) consists of texts collected from image-based exercises and can be searched as in VALICO. In this article, we analyze important aspects of teaching Italian to Vietnamese students: text-related aspects as one text contains 185 words in average, and the interference of Vietnamese language as well as other languages they have learnt (in fact, 108 students speak English, 10 speak French, 8 speak Korean and English or French, 4 speak Chinese, 2 speak Japanese and 2 speak Thai apart from English and Italian).